Nonlinear Analysis of Continuous Composite Beam by Finite Element Method - A. Shalall, Muhanned (Journal of Engineering and Sustainable Development, 2005)
In this paper a composite beam element has been developed. The composite beam element can be used to model the nonlinear behavior of composite beams. The element is implemented in a nonlinear finite element program (written by the researcher) and its implementation is verified by the analysis of continuous beam tested by others. The good agreement between the computed results and experimental data demonstrates accuracy of the used element. It was found that the increase of steel reinforcement gives an increase in ultimate load by 14.3%, also the increase of flange width at plastic hinge region gives an increase in the ultimate load by 39.3%.